Carbon dioxide reforming of methane [microfilm] : the effect of metal, support, temperature and reactant ratio - Chin, Hon Keong (Skudai : Universiti Teknologi Malaysia, 2002)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2002